Total Sky Imager observations and continuous radiation measurements during POLARSTERN cruise ANT-XXVIII/1 with links to images - Engelmann, Ronny; Kanitz, Thomas; Brückner, Marlen; Kleta, Henry; Macke, Andreas (Leibniz-Institut für Troposphärenforschung e.V., Leipzig, 2014)
This data collection contains total Sky Imager observations and continuous radiation measurements during POLARSTERN cruise ANT-XXVIII/1 in 2011.
Keywords: OCEANET-ATMOSPHERE